2015
DOI: 10.1016/j.juro.2014.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Is Top-down vs Bottom-up Radiological Evaluation after Febrile Urinary Tract Infection Really Less Stressful for the Child and Family? Challenging the Dogma

Abstract: Although the top-down approach and repeat voiding cystourethrography cause less anxiety for caregivers, these values do not correlate to pain scale in children. This finding might be due to lack of appropriate evaluation tools of pediatric pain and anxiety. However, the theory that the top-down approach is less invasive, and thus less stressful, requires further research. The Child-Adult Medical Procedure Interaction Scale-Revised data indicate that influences in adult-child interaction are bidirectional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These results indicate that the studies reviewed herein had high methodological quality. The nine observational studies evaluated according to the STROBE statement also demonstrated good methodological quality; 4 conformed with 60-70% of the items (46,47,48,50), 4 conformed with 70-80% of the items (4245), and 1 conformed with >90% of the items (49). …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…These results indicate that the studies reviewed herein had high methodological quality. The nine observational studies evaluated according to the STROBE statement also demonstrated good methodological quality; 4 conformed with 60-70% of the items (46,47,48,50), 4 conformed with 70-80% of the items (4245), and 1 conformed with >90% of the items (49). …”
Section: Resultsmentioning
confidence: 90%
“…The other seven articles were published in different countries. With regard to the methodological designs of the studies, 14 (61%) of the articles were RCTs (2740), 7 (30%) used a cross-sectional design (4147) and 2 (9%) used a cohort design (48,49). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective study Telli et al (page 958) from Turkey evaluated vesicoureteral reflux after febrile urinary tract infection using the top-down approach of dimercaptosuccinic acid scan vs the bottom-up approach of voiding cystourethrography (VCUG). 4 They also compared an additional group of children undergoing repeat VCUG to assess whether vesicoureteral reflux had improved. Children were randomly assigned to the top-down or the bottom-up approach.…”
Section: Bullying and Teasing About Penile Appearancementioning
confidence: 99%